REGION, The journal of ERSA - Special Issue: Well-being in cities and regions: measurement, analysis and policy practices - Paolo Veneri; Arjen J. E. Edzes (REGION, 2017)
This special issue on "Well-being in cities and regions: measurement, analysis and policy practices" is edited by Paolo Veneri (OECD, Paris, France) and Arjen J.E. Edzes (University of Groningen, Groningen, The Netherlands). With the exception of the editorial, all contributions to this special issue have already been published in earlier issues of REGION, for the sake of immediate exposure of the content.
Keywords: 330